Implikationen der US-Steuerreform auf die Hinzurechnungsbesteuerung nach dem AStG - Schümmer, Markus; Leusder, Johannes; Weinrich, Arndt (IStR Internationales Steuerrecht)
1. Effektive Besteuerung von Outbound-Investitionen in den USA 2. Qualifikation von Einkünften als passiv 3. Anwendung des Motivtests auf die USA? 4. Fazit und Ausblick
Keywords: Effektive Besteuerung von Outbound-Investitionen in den USA Qualifikation von Einkünften als passiv Anwendung des Motivtests auf die USA

Demografiegerechtes Verbraucherrecht? – Die Verbraucherstellung im Spiegel sozialer, wirtschaftlicher und technologischer Prozesse - Müller, Stefan; Kluge, Vanessa (Jenseits des Otto Normalverbrauchers – Verbraucherpolitik in Zeiten des „unmanageable consumer“)
Während das Verbraucherprivatrecht an sich recht dicht reguliert ist, hat es demografische Entwicklungen und Kenngrößen bislang noch nicht gezielt aufgegriffen. Doch altersbedingte Einschränkungen oder Sprach- und Technikbarrieren können die praktische Wirksamkeit des Verbraucherrechts in "demografisch geprägten" Sachverhalten in Frage stellen. Der vorliegende Beitrag möchte den Stand des Verbraucherrechts daraufhin untersuchen, ob das Recht demografieblind ist oder ob Anknüpfungspunkte bestehen, welche die Aufnahme individueller Alters-, Migrations- und Kulturerfahrungen bei der Ausformung des Verbraucherrechts gestatten....

Relays: A New Approach for the Finite Departure Problem in Overlay Networks - Scheideler, Christian; Setzer, Alexander (Proceedings of the 20th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS 2018))
A fundamental problem for overlay networks is to safely exclude leaving nodes, i.e., the nodes requesting to leave the overlay network are excluded from it without affecting its connectivity. To rigorously study self-stabilizing solutions to this problem, the Finite Departure Problem (FDP) has been proposed [9]. In the FDP we are given a network of processes in an arbitrary state, and the goal is to eventually arrive at (and stay in) a state in which all leaving processes irrevocably decided to leave the system while for all weakly-connected components in the initial overlay network, all staying processes in that component will still form a weakly connected component. In the standard interconnection model, the FDP is known to be unsolvable by local control protocols, so oracles have been investigated that allow the problem to be solved [9]. To avoid the use of oracles, we introduce a new interconnection model based on relays. Despite the relay model appearing to be rather restrictive, we show that it is universal, i.e., it is possible to transform any weakly-connected topology into any other weakly-connected topology, which is important for being a useful interconnection model for overlay networks. Apart from this, our model allows processes to grant and revoke access rights, which is why we believe it to be of interest beyond the scope of this paper. We show how to implement the relay layer in a self-stabilizing way and identify properties protocols need to satisfy so that the relay layer can recover while serving protocol requests.

Study Effects of Approximation on Conjugate Gradient Algorithm and Accelerate it on FPGA Platform - Filmwala, Tasneem

Programmable Programs? - Designing FPGA Overlay Architectures with OpenCL - Gadewar, Onkar

Patterns of Store-oriented Software Ecosystems: Detection, Classification, and Analysis of Design Options - Jazayeri, Bahar; Zimmermann, Olaf; Küster, Jochen; Engels, Gregor; Kundisch, Dennis; Szopinski, Daniel (The Latin American Conference on Pattern Languages of Programs (SLPLoP))
Software companies nowadays create ecosystems of users and third-party providers around their platforms. They often provide online stores so that the third-party developments can be exposed to users directly. The resulting ecosystems differ significantly from each other in their architectural designs because their providers differ in terms of business goals and contexts. Until now, this architectural diversity and rationale behind it are not well-understood. Therefore, it is not clear which software features contribute to ecosystem’s success with respect to certain business goals and context. This hinders systematic creation of ecosystems in the future. Thus, decision-making becomes too risky; for future ecosystem providers, which may lead to creation of inefficient ecosystems that lack critical features, and for third-party providers to rely on ad-hoc choices while deciding on suitability of an ecosystem for their future career. In this paper, we introduce three design patterns for store- oriented software ecosystems by classifying the design decisions, business goals, and context of 111 store-oriented software ecosystems. Each design pattern provides an architectural solution to achieve a different business goal while supporting a different context. We discuss how the design patterns are applied together in order to achieve more business goals. Our work supports ecosystem and third-party providers by sharing practice-proven architectural solutions, helping them to take informed architectural decisions and reduce technical risks.

A Highly Accurate Energy Model for Task Execution on Heterogeneous Compute Nodes - Lösch, Achim; Platzner, Marco (2018 IEEE 29th International Conference on Application-specific Systems, Architectures and Processors (ASAP))

Information Security Investments: An Exploratory Multiple Case Study on Decision-Making, Evaluation and Learning - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (Computers & Security)
The need to protect resources against attackers is reflected by huge information security investments of firms worldwide. In the presence of budget constraints and a diverse set of assets to protect, organizations have to decide in which IT security measures to invest, how to evaluate those investment decisions, and how to learn from past decisions to optimize future security investment actions. While the academic literature has provided valuable insights into these issues, there is a lack of empirical contributions. To address this lack, we conduct a theory-based exploratory multiple case study. Our case study reveals that (1) firms? investments in information security are largely driven by external environmental and industry-related factors, (2) firms do not implement standardized decision processes, (3) the security process is perceived to impact the business process in a disturbing way, (4) both the implementation of evaluation processes and the application of metrics are hardly existent and (5) learning activities mainly occur at an ad-hoc basis.
Keywords: Information Security Investments; Multiple Case Study; Organizations; Single Loop Learning; Double Loop Learning

A Prototyping Platform to Validate and Verify Network Service Header-based Service Chains - Peuster, Manuel; Schneider, Stefan Balthasar; Christ, Frederic; Karl, Holger (IEEE Conference on Network Function Virtualisation and Software Defined Networks (NFV-SDN) 5GNetApp)

Models and Constructions for Secure Reputation Systems - Juhnke, Jakob

Individual and Social Influences on Professional Learning - Gruber, Hans; Harteis, Christian

Trade-offs in Dynamic Resource Allocation in Network Function Virtualization - Schneider, Stefan Balthasar; Dräxler, Sevil; Karl, Holger (IEEE Global Communications Conference (GLOBECOM 2018))
Dynamic allocation of resources is a key feature in network function virtualization (NFV), enabling flexible adjustment of slices and contained network services to ever-changing service demands. Considering resource allocation across the entire network, many authors have proposed approaches to optimize the placement and chaining of virtual network function (VNF) instances and the allocation of resources to these VNF instances. In doing so, various optimization objectives are conceivable, e.g., minimizing certain required resources or the end-to-end delay of the placed services. In this paper, we investigate the relationship between four typical optimization objectives when coordinating the placement and resource allocation of chained VNF instances. We observe an interesting trade-off between minimizing the overhead of starting/stopping VNF instances and all other objectives when adapting to changed service demands.

A Generic Emulation Framework for Reusing and Evaluating VNF Placement Algorithms - Schneider, Stefan Balthasar; Peuster, Manuel; Karl, Holger (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN 2018))
In recent years, a variety of different approaches have been proposed to tackle the problem of scaling and placing network services, consisting of interconnected virtual network functions (VNFs). This paper presents a placement abstraction layer (PAL) that provides a clear and simple northbound interface for using such algorithms while hiding their internal functionality and implementation. Through its southbound interface, PAL can connect to different back ends that evaluate the calculated placements, e.g., using simulations, emulations, or testbed approaches. As an example for such evaluation back ends, we introduce a novel placement emulation framework (PEF) that allows executing calculated placements using real, containerbased VNFs on real-world network topologies. In a case study, we show how PAL and PEF facilitate reusing and evaluating placement algorithms as well as validating their underlying models and performance claims.

A Fully Integrated Multi-Platform NFV SDK - Schneider, Stefan Balthasar; Peuster, Manuel; Tavernier, Wouter; Karl, Holger (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN 2018))
A key challenge of network function virtualization (NFV) is the complexity of developing and deploying new network services. Currently, development requires many manual steps that are time-consuming and error-prone (e.g., for creating service descriptors). Furthermore, existing management and orchestration (MANO) platforms only offer limited support of standardized descriptor models or package formats, limiting the re-usability of network services. To this end, we introduce a fully integrated, open-source NFV service development kit (SDK) with multi-MANO platform support. Our SDK simplifies many NFV service development steps by offering initial generation of descriptors, advanced project management, as well as fully automated packaging and submission for on-boarding. To achieve multi-platform support, we present a package format that extends ETSI’s VNF package format. In this demonstration, we present the end-to-end workflow to develop an NFV service that is then packaged for multiple platforms, i.e., 5GTANGO and OSM.

Automatic Offloading of Cluster Accelerators - Ceissler, Ciro; Nepomuceno, Ramon; Pereira, Marcio; Araujo, Guido (2018 IEEE 26th Annual International Symposium on Field-Programmable Custom Computing Machines (FCCM))
The sheer amount of computing resources required to run modern cloud workloads has put a lot of pressure on the design of power efficient cluster nodes. To address this problem, Intel (HARP) and Microsoft (Catapult) have proposed CPU-FPGA integrated architectures that can deliver efficient power-performance executions. Unfortunately, the integration of FPGA acceleration modules to software is a challenging endeavor that does not have a seamless programming model. This paper proposes HardCloud (www.hardcloud.org), an extension of the OpenMP 4.X standard that eases the task of offloading FPGA modules to cluster accelerators.
Keywords: pc2-harp-ressources

Do we betray errors beforehand? The use of eye tracking, automated face recognition and computer algorithms to analyse learning from errors. - Harteis, Christian; Fischer, Christoph; Töniges, Torben; Wrede, Britta (Frontline Learning Research)

The journey to proficiency: Exploring new objective methodologies to capture the process of learning and professional development. - Harteis, Christian; Kok, Elen; Jarodzka, Halszka (Frontline Learning Research)

2018 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC) - Cunha, Jácome; Fernandes, Joao Paulo; Kelleher, Caitlin; Mendes, Jorge; Engels, Gregor (Proceedings of 2018 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC), Lisbon, Portugal, October 1-4, 2018)

Towards explaining the popularity of the Business Model Canvas: A dual coding approach - John, Thomas; Szopinski, Daniel (Proceedings of the Multikonferenz Wirtschaftsinformatik 2018 (MKWI), Lüneburg, Germany)

Platform Launch Strategies - Stummer, Christian; Kundisch, Dennis; Decker, Reinhold (Business & Information Systems Engineering)